Islam at the European Court of Human Rights - Fokas, Effie (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2021)
The European Court of Human Rights (ECtHR or, the Court) is a formidable player in the development of legal approaches to Islam: its jurisdictional remit (covering over 800 million people across 47 countries) is vast; it is a standard setter for human rights protection in general on a global scale; and it has a rapidly growing body of case law relevant to Islam which has influenced states’ engagements with Islam within Europe and beyond. Besides the Court’s ‘direct effects’, in terms of impact on relevant legislation, through its decisions to do with Islam, it also has a significant ‘indirect’, social effect though the messages those decisions communicate about Islam and its place in society. This contribution examines the role of the Court in its direct and indirect effects on Islam, law and Europeanisation.